THE RENEWAL OF THE CONSTITUTION OF UZBEKISTAN AND GUARANTEES OF HUMAN RIGHTS - Khasanov, Boburbek (Oriental Journal of History, Politics and Law, 2025)
This article analyzes the role of the Constitution of the Republic of Uzbekistan, updated in 2023, in strengthening human rights and freedoms. In the new edition, human dignity, worth, freedom and equality are recognized as priority values, and the system of legal guarantees has been improved. The article highlights the main directions of constitutional reforms, their compliance with international standards and their significance in the development of civil society.